Effect of Sea Water on Human Hair - zhang, jiashu. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Igor Sokolov.; Committee: Anil Saigal, and Fiorenzo Omenetto.; Keyword: Mechanical engineering.